Cardiopulmonary Resuscitation Techniques in the COVID-19 Pandemic Era: Literature Review - Arista Maisyaroh; Syaifuddin Kurnianto; Eko Prasetya Widianto; Primasari Mahardika Rahmawati; Retno Sari Nurhabibah (KHD Production, 2023)
Cardiac resuscitation in the era of the COVID-19 pandemic meets its challenges; in addition to the high prevalence of cardiac and pulmonary arrest events in these patients, the transmission rate to health workers who carry out CPR assistance is also relatively high. Therefore, it is necessary to develop CPR techniques in COVID-19 patients that can increase the success of CPR and reduce transmission rates. The purpose of the study was to explain how CPR techniques are in COVID-19 patients. The literature review method through data collection with an electronic database and evaluation of the literature review will use Critical Appraisal to test validity. Data collection with electronic databases was conducted through PubMed, Tailor, Francis, and Google Scholar with the keyword